Emerging Diversity of Channelrhodopsins and Their Structure-Function Relationships - Govorunova, Elena G.; Sineshchekov, Oleg A.; Spudich, John L. (Frontiers in Cellular Neuroscience, 2022)
Cation and anion channelrhodopsins (CCRs and ACRs, respectively) from phototactic algae have become widely used as genetically encoded molecular tools to control cell membrane potential with light. Recent advances in polynucleotide sequencing, especially in environmental samples, have led to identification of hundreds of channelrhodopsin homologs in many phylogenetic lineages, including non-photosynthetic protists. Only a few CCRs and ACRs have been characterized in detail, but there are indications that ion channel function has evolved within the rhodopsin superfamily by convergent routes. The diversity of channelrhodopsins provides an exceptional platform for the study of structure-function evolution in membrane proteins. Here we review the current state of channelrhodopsin research and outline perspectives for its further development.